(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A simple mathematical model to characterise the supercritical extraction process has been proposed in this paper. This model is primarily based on two mass transfer mechanisms: solubility and diffusion. The model assumes two districts mode of extraction: initial constant rate extraction that is controlled by solubility and falling rate extraction that is controlled by diffusivity. Effects of extraction parameters such as pressure and temperature on the extraction of oil have also been studied. The proposed model, when compared with existing models, shows better agreement with the experimental results. The proposed model developed has been applied for both high initial oil content material and low initial oil content material.